COVID-19 vaccine hesitancy: misinformation and perceptions of vaccine safety - Kricorian, Katherine; Civen, Rachel; Equils, Ozlem (Human vaccines & immunotherapeutics, 2022)
Despite COVID-19's devastating toll, many Americans remain unwilling to receive the COVID-19 vaccine. The authors conducted a US national survey to understand the health literacy of adults regarding the vaccine, as well as their COVID-19 beliefs and experiences. People who believed the COVID-19 vaccine was unsafe were less willing to receive the vaccine, knew less about the virus and were more likely to believe COVID-19 vaccine myths. On average, they were less educated, lower income, and more rural than people who believed the vaccine is safe. The results highlight the importance of developing clear health communications accessible to individuals from varied socioeconomic and educational backgrounds.